2015
DOI: 10.3390/agronomy5030447
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Crop Plants: Transport and Redistribution Processes on the Whole Plant Level

Abstract: Abstract:Copper, zinc, manganese, iron, nickel and molybdenum are essential micronutrients for plants. However, when present in excess they may damage the plant or decrease the quality of harvested plant products. Some other heavy metals such as cadmium, lead or mercury are not needed by plants and represent pollutants. The uptake into the roots, the loading into the xylem, the acropetal transport to the shoot with the transpiration stream and the further redistribution in the phloem are crucial for the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(113 citation statements)
references
References 118 publications
(254 reference statements)
6
107
0
Order By: Relevance
“…Remobilization and re-translocation of Fe via phloem to youngest leaves can reduce the severity of the chlorosis severity. However, an extremely poor redistribution via the phloem was found for Fe (Page and Feller, 2015). solutes (Offler et al, 2003).…”
Section: Different Mobility Of Nano and Bulk Fe In The Phloemmentioning
confidence: 97%
See 1 more Smart Citation
“…Remobilization and re-translocation of Fe via phloem to youngest leaves can reduce the severity of the chlorosis severity. However, an extremely poor redistribution via the phloem was found for Fe (Page and Feller, 2015). solutes (Offler et al, 2003).…”
Section: Different Mobility Of Nano and Bulk Fe In The Phloemmentioning
confidence: 97%
“…solutes (Offler et al, 2003). In an experiment using 59Fe it has been observed that Fe is transported with the transpiration stream to minor leaf veins, followed by an accumulation in non-vascular tissues (Page and Feller, 2015) revealing a low xylem-phloem exchange for this element. In our work, however, probably due to its lower size, nano Fe was likely able to use this pathway more effectively than bulk Fe.…”
Section: Different Mobility Of Nano and Bulk Fe In The Phloemmentioning
confidence: 99%
“…Moreover, inner leaves contained relatively higher Ni concentrations than the outer leaves. Such a result probably shows that cabbage probably needs Ni as a beneficial element (Welch & Shuman, 1995& Yusuf et al, 2011 since Ni is highly phloem-mobile (Page and Feller, 2015). Nickel concentrations exceed the permissible level (i.e.…”
Section: Nickel In Cabbagementioning
confidence: 99%
“…The roots are the main site where mineral nutrient uptake takes place, and the mobilization of such nutrients from the roots to other tissues may depend on the nature of the mineral element. For instance, only a small amount of heavy metals reach the shoots and they stay mainly in the roots, since heavy metals show a low solubility at the root surface and in the root apoplast, or to compartmen-tation in cells avoiding release to the xylem (Page and Feller, 2015).…”
Section: Micronutrients Display Different Concentration Patterns In Pmentioning
confidence: 99%